An Analysis of EFL Students’ Online Reading Habits - Muhamad Hasbi; Santi Novia Wulansari (Cipta Pustaka Nusantara, 2025)
With the fact that current EFL students are digital natives and go online frequently, conducting online-based English skill learning activities is encouraged. As reading is one of the fundamental skills to be developed in the early stage of EFL learning, preparing online-based reading activities for the students can be a good move. This study identifies EFL students’ reading habits, which specifically investigates their source of online reading, their online reading frequency, and factors that influence that habit. The study was conducted in an Islamic state university with a class of 30 English department students as the subject. Questionnaires and interviews were used to gather the data. The study found that students majorly read online from English learning websites and social media, with reading from social media happening more frequently than the other, placing fulfilling college tasks and entertainment purposes as the primary motives of their online reading habits.